Pemberdayaan Karang Taruna Desa Palur melalui Inovasi MOSbyeCandella (Lilin Antinyamuk dari Minyak Jelantah) - Tatiana Siska Wardani; Erna Chotidjah Suhatmi; Agung Widiastuti; Nesya Sucitra; Faizah Ariqoh; Muhhamad Aminulloh (I-Com: Indonesian Community Journal, 2024)
Cooking oil that is used more than three times will be dangerous for the body. This is due to damage to the oil which will affect the quality and nutritional value of the food being fried and can have an impact on health. Karang Taruna Saras Muda is a community group consisting of young people in Palur Village, Sukoharjo Regency who are active in various activities, one of which is helping the community in creating a clean environment. The objectives of this PKM activity are (a) The aim of this empowerment is to provide education through socialization and training on making anti-mosquito candles (MOSquito BYE CANDELLA) to Karang Taruna Saras Muda partners in Palur Village and through mentoring to provide partners with the opportunity to learn entrepreneurship in utilizing the results of wax products from used cooking oil so that they can be accepted on the market. The PKM method starts with 3 stages, namely socialization, training, with the application of appropriate technology and marketing management training as well as mentoring and evaluation. The result of this PKM is that by evaluating the PKM implementation program, the aim is for partners to gain insight, knowledge and skills that are useful in managing used cooking oil waste and in particular for making anti-mosquito candles (Mos Bye Candella). The PKM activity implementation team hopes that this activity can increase the economic value of used cooking oil. Based on the results of PKM activities through making anti-mosquito candles from used cooking oil waste for the Palur Village Youth Organization, it went well and smoothly. The suggestion from PKM is to implement other innovations by utilizing used cooking oil waste to make other products that can be used by the wider community.